Experience report: an inquiry-based instructional sequence on arthropods in high school: Experience report: an inquiry-based instructional sequence on arthropods in high school (Health and Biosciences, 2025)
This experience report aimed to investigate how an instructional sequence grounded in Inquiry-Based Learning (IBL) can contribute to the development of scientific competencies and pro-conservation attitudes among high-school students, thereby addressing gaps identified in environmental and zoological education. The intervention was carried out with two final-year classes at a public high school in Serra (ES), Brazil, involving 45 students aged 16–18. The methodology comprised four 2-hour meetings: (1) problematization of global arthropod declines and hypothesis formulation; (2) field sampling in green areas surrounding the school using pitfall traps and manual capture; (3) taxonomic analysis and a structured debate on anthropogenic impacts; and (4) planning of conservation actions for the school surroundings. Data were collected through field notebooks, collaborative murals and pre- and post-intervention questionnaires, and were analyzed quantitatively (mean correct answers in conceptual assessments) and qualitatively using Content Analysis. Results showed an increase in mean correct answers from 48% (pre-test) to 90% (post-test) and the emergence of attitudinal categories such as empathy toward arthropods, ecological awareness and motivation for conservation. Improvements were also observed in evidence-based argumentation skills and student protagonism. We conclude that the use of IBL and active methodologies combined with fieldwork and structured debate strengthens concept consolidation and the promotion of socio-environmental attitudes even in contexts of limited resources. For future implementations, we recommend expanding technical-scientific partnerships, integrating citizen-science platforms, and conducting longitudinal follow-up of the proposed conservation actions.
Keywords: inquiry-based learning; environmental education; active methodologies; biodiversity